The Effect of the Think Pair Share Cooperative Learning Model on the Mathematics Learning Outcomes of Phase F Students in the Computer and Network Engineering Program at SMK Negeri 5 Padang - Leti Murni Laia; Dina Novarina Perdana; Nela Sari Yolanda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The low mathematics learning outcomes of Phase F students in the Computer and Network Engineering Department at SMK Negeri 5 Padang constitute one of the problems encountered in the learning process. This condition is characterized by low student participation, limited interaction and cooperation among students, a lack of confidence in asking questions, and a learning process that is still dominated by teacher explanations. This study aimed to determine whether the mathematics learning outcomes of students taught using the Think Pair Share cooperative learning model were better than those of students taught using conventional instruction. This study employed a quantitative approach with a quasi-experimental method. The population consisted of all Phase F students in the Computer and Network Engineering Department at SMK Negeri 5 Padang during the 2025/2026 academic year, totaling 57 students from two classes. The sampling technique used was saturated sampling, in which all members of the population were included as research participants. One class was assigned as the experimental class and received instruction using the Think Pair Share model, while the other class served as the control class and received conventional instruction. The research instrument was a mathematics achievement test in the form of essay questions that had undergone validation and pilot testing. The research data were analyzed using normality testing, homogeneity of variance testing, and a one-tailed independent-samples t-test. Because the data were normally distributed and homogeneous, hypothesis testing was conducted using the t-test. The results showed that >(4.24 > 1.68 at a significance level of α=0.05. Therefore, H₀​ was rejected and ​ H₁ was accepted. Based on these findings, it can be concluded that the use of the Think Pair Share cooperative learning model had a positive effect on the mathematics learning outcomes of Phase F students in the Computer and Network Engineering Department at SMK Negeri 5 Padang.